2022
DOI: 10.3390/rs14051272
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based Multispectral Image Reconstruction from Single Natural Color RGB Image—Enhancing UAV-Based Phenotyping

Abstract: Multispectral images (MSIs) are valuable for precision agriculture due to the extra spectral information acquired compared to natural color RGB (ncRGB) images. In this paper, we thus aim to generate high spatial MSIs through a robust, deep-learning-based reconstruction method using ncRGB images. Using the data from the agronomic research trial for maize and breeding research trial for rice, we first reproduced ncRGB images from MSIs through a rendering model, Model-True to natural color image (Model-TN), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…To the best of the authors' knowledge, this paper presents a novel and comprehensive approach that significantly differs from existing works in predicting crop yields. While previous studies have explored various methodologies, such as statistical modeling [7], and deep learning techniques [13,14], none have integrated multi-temporal images and machine learning algorithms in the manner proposed here.…”
Section: Our Main Contributionmentioning
confidence: 99%
“…To the best of the authors' knowledge, this paper presents a novel and comprehensive approach that significantly differs from existing works in predicting crop yields. While previous studies have explored various methodologies, such as statistical modeling [7], and deep learning techniques [13,14], none have integrated multi-temporal images and machine learning algorithms in the manner proposed here.…”
Section: Our Main Contributionmentioning
confidence: 99%
“…However, they also revealed that the method provides accurate outputs only until appearance of senescence. Paper [10] proposes a deep-learning-based method to generate a multi-spectral (MSI) data from pure RGB images. They first reproduced RGB images from multi-spectral ones through a rendering model, which was built with a benchmark hyperspectral image dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Multispectral and hyper-spectral aerial photographs are important in crop management because of their potential to demonstrate crop development. References [25,26] propose a new energy-balanced algorithm, and use the landsat8 images to estimate the potato crop yield.…”
Section: Models (Version)mentioning
confidence: 99%